Silencing of Antichondrogenic MicroRNA‐221 in Human Mesenchymal Stem Cells Promotes Cartilage Repair In Vivo. (27th March 2016) - Lolli, Andrea; Narcisi, Roberto; Lambertini, Elisabetta; Penolazzi, Letizia; Angelozzi, Marco; Kops, Nicole; Gasparini, Simona; van Osch, Gerjo J.V.M.; Piva, Roberta
Abstract : There is a growing demand for the development of experimental strategies for efficient articular cartilage repair. Current tissue engineering‐based regenerative strategies make use of human mesenchymal stromal cells (hMSCs). However, when implanted in a cartilage defect, control of hMSCs differentiation toward the chondrogenic lineage remains a significant challenge. We have recently demonstrated that silencing the antichondrogenic regulator microRNA‐221 (miR‐221) was highly effective in promoting in vitro chondrogenesis of monolayered hMSCs in the absence of the chondrogenic induction factor TGF‐β. Here we investigated the feasibility of this approach first in conventional 3D pellet culture and then in an in vivo model. In pellet cultures, we observed that miR‐221 silencing was sufficient to drive hMSCs toward chondrogenic differentiation in the absence of TGF‐β. In vivo, the potential of miR‐221 silenced hMSCs was investigated by first encapsulating the cells in alginate and then by filling a cartilage defect in an osteochondral biopsy. After implanting the biopsy subcutaneously in nude mice, we found that silencing of miR‐221 strongly enhanced in vivo cartilage repair compared to the control conditions (untreated hMSCs or alginate‐only). Notably, miR‐221 silenced hMSCs generated in vivo a cartilaginous tissue with no sign of collagen type X deposition, a marker of undesired hypertrophic maturation. Altogether our data indicate that silencing miR‐221 has a prochondrogenic role in vivo, opening new possibilities for the use of hMSCs in cartilage tissue engineering. Stem Cells 2016;34:1801–1811